2014
DOI: 10.1103/physrevlett.112.135502
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Controlled Circular Second-Harmonic Generation from Metal Hole Arrays with Threefold Rotational Symmetry

Abstract: The discrete rotational symmetry of nanostructures provides a powerful and simple guiding principle for designing the second-harmonic generation process in nonlinear metamaterials. We demonstrate that, in achiral nanostructures with threefold rotational symmetries, a circularly polarized fundamental beam produces a countercircularly polarized second-harmonic beam. In this case, the polarization state of the second harmonic is determined in a very simple manner. We also demonstrate how rotational symmetries in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
103
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 34 publications
4
103
0
Order By: Relevance
“…For a circularly polarized FW propagating along the three-fold axis of a c-cut β-BBO crystal, we find that the SHG signal with the same polarization state as the FW (LCP-LCP and RCP-RCP) is much weaker than that with the polarization state opposite to the FW (LCP-RCP and RCP-LCP). This agrees well with the selection rules for harmonic generations of circularly polarized light demonstrated in previous works [29][30][31][32][33][34][35] . Theoretically, SHG of the same spin as the FW should be forbidden for a crystal with C3 rotational symmetry.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…For a circularly polarized FW propagating along the three-fold axis of a c-cut β-BBO crystal, we find that the SHG signal with the same polarization state as the FW (LCP-LCP and RCP-RCP) is much weaker than that with the polarization state opposite to the FW (LCP-RCP and RCP-LCP). This agrees well with the selection rules for harmonic generations of circularly polarized light demonstrated in previous works [29][30][31][32][33][34][35] . Theoretically, SHG of the same spin as the FW should be forbidden for a crystal with C3 rotational symmetry.…”
supporting
confidence: 79%
“…Although equation (4) shows that the Doppler shift is directly related to the harmonic generation order, the rotational symmetry of the nonlinear crystal also plays an important role. The reason is that crystals of certain rotational symmetry allow only nonlinear processes of certain orders according to the selection rule pertaining to harmonic generations with circularly polarized FWs 33,34 . Specifically, it has been shown that the allowed nonlinear generation orders are given by n = ml ± 1, where m is the rotational symmetry order, l is an arbitrary positive integer, and '+' and '−' signs correspond to the harmonic generation signal with the same and the opposite circular polarization as that of the fundamental beam, respectively 33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typical examples includes L-shaped gold nanoparticle [142,143], T-shaped nanoparticle [144], split-ring resonator (SPR) with electric or magnetic dipole resonance [145][146][147], and silver triangular nanoprisms and nanoholes [148,149]. A symmetry-breaking metasurface not only significantly enhances its nonlinear optical response but also shows strong spin-selectivity in the nonlinearly generated light [150]. Polarization-dependent selection rules for high harmonic generations on a metasurface have also been extensively studied [151].…”
Section: Symmetry-related Applications With Spin-orbit Interactionmentioning
confidence: 99%
“…[24][25][26][27][28] It has already been demonstrated that for a circularly polarized fundamental wave (FW) propagating along the axis of molecules or artificial nanostructures with n-fold rotational symmetry, the allowed order (m) of harmonic generation can be determined from a selection rule m = nl ± 1, where l is an arbitrary integer, and the "+" and "-" signs represent that harmonic generation and FW possess the same and opposite circular polarization states, respectively. [29][30][31] In our case, the gammadion-shaped meta-atoms have four-fold rotational (C4) symmetry, and are arranged in a square lattice such that the symmetry of the structures and the lattice are consistent with each other [ Fig. 1(a)].…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%